“How Lucky You Are Never to Know What It Is to Grow Old”: Witch as Fourth-Wave Feminist Monster in Contemporary Fantasy Film - Schubart, Rikke (Nordlit, 2019)
This article focuses on the figure of an aging and powerful witch pitted against younger women in three contemporary fairy-tale movie adaptations: Snow White and the Huntsman (dir. Rupert Sanders, 2012), Hansel & Gretel: Witch Hunters (dir. Tommy Wirkola, 2013), and Maleficent (dir. Robert Stromberg, 2014). Each film transforms the aging witch from stock villain to a more nuanced character. This revision is intriguing for its concern with power and gender and for a reflection of contemporary debates about age and power within so-called wave feminism. The article uses two frames. The first is feminism and ageism, focusing on wave feminism and aging, and the second is the trope of the witch, drawing from fairy-tale studies, social history, and social anthropology. The article reads conflict between an aging witch and a young woman as a clash of feminist waves, and the witch’s ‘monstrosity’ as her refusal to be sidelined in a world obsessed with youth.